Análise do padrão de expansão da agricultura no estado de Goiás no período de 1970 a 1995 - Abreu, José Marcelo de (2001)
In this work, the contributions of the agricultural sector to the economic development of the State of Goiás were observed. Its scope occurred in the expansion of its agriculture based on the pattern of technological progress, from the facilities offered by the public power, from the year of 1970 The insertion of the Goiás agricultural economy to the coffee economy of the Center Sul, as an absorber of Goiás products at the moment of its organization and its socio-economic relations of dependence, was analyzed. A retrospective analysis of the recent transformation in Brazilian agriculture was made based on the penetration of capitalism in the countryside through state intervention. This sector, in Goiás, is analyzed through the pattern and growth rates of the area, production and yields of the main crops of the state's agricultural production, over a period of 25 years. The modernization of Goiana agriculture has the same characteristics as those observed in the process of modernization of Brazilian agriculture, whose pattern only occurred with the intensive use of mechanization and modern inputs. The model of expansion and modernization of this agriculture is the same adopted in Brazil. Both met specific interests of the Green Revolution, while constituting the insertion of agriculture into capitalism. Data from the 70's reveal the beginning of soybean crop expansion in Goiás, due to the emergence of new production technologies. There was a close link between rural credit policy and the modernization of agriculture. It was found that in the selected crops - rice, corn and soybean - were the ones that most benefited from the subsidized credit policy in the period. Even with the abrupt reduction in credit subsidies, from the early 1980s, Goiás agriculture continued to grow due to the reorganization capacity of farmers. Therefore, the expansion and development of Goiás agriculture, through the process of modernization, acquired from 1970 to 1995, significant importance due to the spatial reorganization.